Sport and nutrition - Trikojus, Tom; Trikojus, Tom (Victoria : Video Education Australasia, 2000)
This video explores the ways elite sports people use nutrition to give themselves on extra edge.
Editors, Shasha Trikojus, Trikojus Tom, Joel de Courey Browne; executive producer, Stephen Skou
Narrator: Jenny Tudor
Keywords: Food; Nutrition disorder